THE EFFECT OF PATIENT EXPERIENCE AND PROMOTION STRATEGY ON OUTPATIENT LOYALTY WITH WORD OF MOUTH AS A MEDIATING VARIABLE - Luciawati; Hery Winoto Tj (CV. Radja Publika, 2026)
To survive in the increasingly tight healthcare competition, hospitals must maintain clinical and operational service quality to build long-term patient loyalty. This study examines the effect of patient experience and promotion strategies on outpatient loyalty, both directly and indirectly through word of mouth (WOM) as a mediating variable. A purposive sampling technique was used in the data collection process, involving 180 outpatient respondents at RS Sentra Medika Cikarang. Data analysis was performed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) via SmartPLS 3.0 software. The test results show that patient experience and promotion strategies are essential aspects that significantly drive positive word of mouth. Furthermore, patient experience and word of mouth have a significant positive direct effect on patient loyalty. In contrast, the promotion strategy does not directly influence patient loyalty. Mediation analysis reveals that word of mouth partially mediates the effect of patient experience on loyalty, while it fully mediates the impact of promotion strategy on patient loyalty.